An insectual perspective: text, theory, and politics in Tom McCarthy's fiction – a conversation. Issue 1 (2nd January 2021) - Malreddy, Pavan Kumar
ABSTRACT: Since Zadie Smith's pronouncement of Tom McCarthy's fiction as an exemplar of the contemporary avant-garde in 2008, many critics have enthusiastically – at times hastily – embraced the label, classifying him variedly as nihilist, late modernist or even a pessimist. Yet, much of the existing criticism on McCarthy has tended to focus on the formal-aesthetic tropes and the generic classification of his novels. Given his penchant for hermeneutics and deconstruction, McCarthy may well entertain such wide array of perspectives and readings, even if he might disagree with a neat categorisation of his work – as he does in this interview. This conversation, which took place in a public park in central Berlin, moves away from the undue scholarly emphasis on formalistic devices and experimental nature of McCarthy's work, and attempts to bring the politics of theory, text, and postcolonialism in his writing to the reader's attention.